Frontal Mucocele With Proptosis: DrafIIa Approach - Abdullah, Siti Nazira; Khalid, Mohamad Azizul Fitri; Ramli, Ramiza Ramza (International Journal of Human and Health Sciences (IJHHS), 2021)
Paranasal sinus mucocele commonly involved fronto-ethmoidal region rather than other due to its narrow anatomical drainage outflow, which put them at a higher tendency to get obstructed. Usually, it arises from an identifiable cause such as a history of endonasal surgery, facial trauma or background of nasal allergy or rhinosinusitis. Rarely patient presented with primary frontal mucocele, and its presentation depending on the mucocele location and extension with surrounding mass effect. Treatment is based on restoration of frontal sinus drainage and ventilation or towards a more radical and definitive approach which is sinus obliteration. Risk and benefits between these two need to be taken into consideration. We present a case of primary frontal mucocele with gradual onset of unilateral eye proptosis which first presented solely with ophthalmic symptoms. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 366-371